(untitled) (KONFERENSIYA, 2025)
The paper considers about the characteristics of the diplomatic terms and diplomatic language in general. The relevance of this research is due to the need to study diplomatic terms present in the political texts and sources as a special object of translation activity. The article offers some examples of diplomatic notions and their equivalents in Russian